Complete Intracranial Arterial and Venous Blood Flow Evaluation with 4D Flow MR Imaging - Hope, M.D.; Purcell, D.D.; Hope, T.A.; von Morze, C.; Vigneron, D.B.; Alley, M.T.; Dillon, W.P. (American Journal of Neuroradiology, 2009)
SUMMARY: Time-resolved, 3D velocity–encoded MR imaging (4D Flow) allows for the acquisition of dynamic, multidirectional data on blood flow and has recently been used for the evaluation of intracranial arterial flow. Using a 3T system with optimization of both temporal resolution and k-space subsampling with a combination of parallel imaging and cut-corner acquisition, we present the clinical assessment of a patient with an arteriovenous malformation by providing complete intracranial arterial and venous coverage in a reasonable scan time.